ANALISIS PENERAPAN SAK ETAP TERHADAP PENYAJIAN LAPORAN KEUANGAN BUMDES SUMBER REJEKI DESA JIWAN - Nur Okpa, Fitriani (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
This study aims to determine the condition of the financial statements and to analyze whether the presentation of the financial statements of BUMDes Sumber Rejeki is in accordance with the applicable SAK ETAP. The data analysis technique of this research used descriptive qualitative methods with data collection methods through observation, interviews, and library research. The results of the study stated that the accountability report prepared by the Sumber Rejeki BUMDes was not based on SAK ETAP. The financial statements prepared consist of a balance sheet, income statement, statement of changes in equity and cash flow statement, BUMDes does not present notes on financial statements in the accountability report, and lack of knowledge among BUMDes Sumber Rejeki managers. It is expected that BUMDes employ employees who are familiar with the accounting field, as well as attend training or socialization regarding the presentation of financial statements in accordance with SAK ETAP.